Exploratory Factor Analysis of Financial Entrepreneurial Competencies for Technical College Programs for a Sustainable Self-employment - Ibrahim Muhammad, Abubakar; Bin Kamin, Yusri; Husna Binti Abd. Wahid, Nur (International Journal of Psychosocial Rehabilitation, 2020)
The study was aimed at exploring and summarizing Financial Entrepreneurial Competencies (FECs) through Exploratory Factor Analysis (EFA) for the development of a model for technical college programs in the North-West geo-political zone of Nigeria. The quantitative research approach was used to develop insight into stakeholders’ perspectives: teachers and entrepreneurs. The study used survey questionnaires. The sample of the study involved 331 participants, including 249 technical college teachers and 82 SME entrepreneurs from the three states in the zone. Statistical Package for Social Sciences (SPSS) version 24 was used to analyze the data collected, and a value of 0.72 Cronbach’s alpha was achieved. From the EFA, the study found that a three-factor structure is an appropriate method for describing the elements of FECs. Additionally, the value for the KMO measure of sampling adequacy amounted to 0.821, and the value for Bartlett’s test was significant at the 0.000 level. This indicated that the correlation between the variables was sufficiently large for factor analysis. The study also identified 61.99% as a total variance explained, which is greater than the accepted threshold value. All the 12 items had a sizable inter-item correlation > 0.4, except FEC9 and FECP14, which were eventually removed due to the complexity of the variable and were omitted in EFA. The study also highlights that it has been concluded FECs are worthy of inclusion into technical college programs as entrepreneurial competencies required by technical college students for self-employment in Nigeria.